HISTORIOGRAPHY OF THE BANKING ACTIVITIES OF THE TURKESTAN GOVERNOR-GENERALSHIP IN THE 40S AND 90S OF THE 20TH CENTURY - Чориев, Шохрух (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
The article is devoted to the historiography of the banking activities of the Turkestan Governor-Generalship in the 20-40s of the XX century. The work analyzes key works dedicated to the study of the region's banking system during this period, as well as the changes in the scientific approach to researching this issue at different stages of history. Particular attention is paid to the interpretation of the banking system's influence on the economy, social relations, and the development of financial institutions in Turkestan by various historical schools and scientific directions.